2007
DOI: 10.1017/s1355617707070610
|View full text |Cite
|
Sign up to set email alerts
|

A predominance of category deficits for living things in Alzheimer's disease and Lewy body dementia

Abstract: Although semantic memory impairment is well documented in patients with dementia of the Alzheimer's type, questions remain as to whether the deficit extends to other forms of dementia and whether it differentially affects different domains of knowledge. We examined category naming on two tasks (picture naming and naming-to-description) in patients with Alzheimer's disease (AD: n 5 11), Lewy body dementia (DLB: n 5 11) and healthy elderly matched controls (n 5 22). The DLB and AD groups showed significantly wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 59 publications
0
9
0
Order By: Relevance
“…In picture naming, the AD patients made more errors in natural/living items in all assessment times for semantic errors and also for crosslanguage intrusions at follow-up, replicating one of the most frequent category-specific deficits in AD (e.g., Chertkow, Whatmough, Saumier, & Duong. 2008;Laws, Crawford, Gnoato, & Sartori, 2007;Tippett, Meier, Blackwood, & Diaz-Asper, 2007;Zannino, Perri, Carlesimo, Pasqualetti, & Caltagirone, 2002). However, this effect was less consistent in translation, suggesting that the semantic properties of the words are task sensitive.…”
Section: Discussionmentioning
confidence: 92%
“…In picture naming, the AD patients made more errors in natural/living items in all assessment times for semantic errors and also for crosslanguage intrusions at follow-up, replicating one of the most frequent category-specific deficits in AD (e.g., Chertkow, Whatmough, Saumier, & Duong. 2008;Laws, Crawford, Gnoato, & Sartori, 2007;Tippett, Meier, Blackwood, & Diaz-Asper, 2007;Zannino, Perri, Carlesimo, Pasqualetti, & Caltagirone, 2002). However, this effect was less consistent in translation, suggesting that the semantic properties of the words are task sensitive.…”
Section: Discussionmentioning
confidence: 92%
“…4143 Investigators have described patients with herpes simplex encephalitis and bilateral inferior temporal lobe damage who have had significantly greater difficulty in recognizing and naming animals and food items than with inanimate objects. 4449 Differential impairment for living things has also occurred among head-injury patients and in SD.…”
Section: Discussionmentioning
confidence: 99%
“…This dissociation of impairment has been taken as evidence that different superordinate categories are processed in neuroanatomically distinct cortical regions. However, selective deficits have also been observed in patients with less focused neural damage (e.g., Alzheimers: [11], [12]), raising the possibility that selective deficits can arise from unfocussed damage to a more distributed system. Furthermore, while neuroimaging studies have identified regions of activation specific to animates or inanimates [13], [14], these categories also activate common regions, with only small and inconsistent differences between domains [15].…”
Section: Introductionmentioning
confidence: 99%